Immunomodulator use does not prevent first loss of response to anti‐tumour necrosis factor alpha therapy in inflammatory bowel disease: long‐term outcomes in a real‐world cohort. Issue 6 (11th June 2019) - Varma, Poornima; Rajadurai, Anton S.; Holt, Darcy Q.; Devonshire, David A.; Desmond, Chris P.; Swan, Michael P.; Nathan, Debra; Shelton, Edward T.; Prideaux, Lani; Sorrell, Catherine; Rusli, Ferry; Crantock, Luke R. F.; et al.
Abstract: Background: Recent prospective studies suggest combination therapy with immunomodulators improves efficacy, but long‐term data is limited. Aim: To assess whether anti‐tumour necrosis factor alpha (anti‐TNF) monotherapy was associated with earlier loss of response (LOR) than combination therapy in a real‐world cohort with long‐term follow up. Methods: A retrospective audit was conducted of inflammatory bowel disease patients receiving anti‐TNF therapy in a tertiary centre and specialist private practices. All patients with accurate data for anti‐TNF commencement and adequate correspondence to determine end‐points were included. Outcomes measured included time to first LOR, causes and biochemical parameters. Results: Two hundred and twenty‐four patients were identified; 139 (62.1%) on combination therapy and 85 (37.9%) on monotherapy. Forty‐five percent of patients had LOR during follow up until a maximum of 8.5 years; 59.4% on combination therapy and 40.6% on monotherapy ( P = 0.533). The median time to LOR was not different between groups; 1069 days for combination therapy and 1489 days for monotherapy ( P = 0.533). There was no difference in time to LOR between patients treated with different combination regimens or different anti‐TNF agents. Conclusion: In this large cohort of patients in a real‐world setting, patients treated with anti‐TNF monotherapy had similar rates of LOR as patients on anti‐TNF combination therapy, at both short‐ and long‐term follow up.